Enhancing Athletes' Physical Performance Through the Intervention of 'Tiliaya' Food Supplement Derived from Traditional Food Reformulation - Yoyanda Bait; Hartono Hadjarati; Siti Aisa Liputo (Universitas Negeri Semarang, 2025)
Background: Athlete nutrition can indirectly improve athlete performance. One of the efforts to improve athlete nutrition is by providing additional food such as Tiliaya. Tiliaya is a traditional Gorontalo food that is believed to increase stamina, because it has high calories. This study aims to increase the physical activity of athletes through the intervention of reformulated tiliaya products. Method: This study used 20 respondents of Gorontalo Student Training and Education Program (STEP) Taekwondo athletes. The intervention was carried out for 3 months with the parameters measured, namely nutritional status based on body mass index, measurement of cholesterol levels (Cholesterol OxidasePhenol Aminophenazone/CHOD-PAP) and VO2max, before and after the intervention. Result: The results of the athlete's blood cholesterol test showed that there were 75.00% in the normal category and 25.00% in the high category. The results of T-Test of Cholesterol level and VO2Max significant for treatment group and not significant for control group. Conclusion: This study demonstrates that the intervention of a reformulated food supplement, Tiliaya (using fiber creme as a substitute for coconut milk), has a significant impact on improving the physical fitness of STEP taekwondo athletes in Gorontalo, particularly by reducing total cholesterol levels and enhancing VO2max capacity